Phototherapy for Treating Chronic Spontaneous Urticaria - Widyastuti, Zilpa; Oktavriana, Triasari (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: Chronic spontaneous urticaria (CSU) is a disease characterized by the onset of wheals, angioedema and/or both for more than 6 weeks. The clinical characteristics of CSU include wheals and flares that are erythematous or skin- colored. The most frequently used medical therapy is second-generation H1 antihistamines followed by first-generation H1 antihistamines. CSU is currently treated with phototherapy utilizing narrowband ultraviolet B (NB-UVB). Case: A 36-year-old woman presented to the Dermatology and Venereology Outpatient Clinic of DR. Moewardi Hospital, Surakarta, with itchy reddish bumps all over her body since 6 months ago. A dermatology examination obtained multiple erythematous-based urticaria varying in size on her anterior and posterior trunks. We treated this patient with a combination of antihistamines and NB-UVB phototherapy at 200 mJ/cm2 weekly for a month. Significant clinical improvement was observed at week 4 of therapy. Discussion: In the treatment of chronic spontaneous urticaria, NB-UVB phototherapy serves as an adjuvant therapy. It acts as a suppressor of the systemic immune response which reduces the release of histamines and pro-inflammatory mediators, prevents mast cell apoptosis in the dermis, and regulates Th1 as well as Th2. The dose may start at 200 mJ/cm2 then increase by 10-20% for each visit. Conclusion: The combination of antihistamines and NB-UVB has a significant effect on treating chronic spontaneous urticaria.